C lamp-Cru shin g versus s tapler h epatectomy for transection of the parenchyma in elective hepatic resection (CRUNSH) - a randomized controlled trial (NCT01049607) - Rahbari, Nuh Nabi; Elbers, Heike; Koch, Moritz; Bruckner, Thomas; Vogler, Patrick; Striebel, Fabian; Schemmer, Peter; Mehrabi, Arianeb; Büchler, Markus W.; Weitz, Jürgen (BMC surgery, 2011)
Background: Hepatic resection is still associated with significant morbidity. Although the period of parenchymal transection presents a crucial step during the operation, uncertainty persists regarding the optimal technique of transection. It was the aim of the present randomized controlled trial to evaluate the efficacy and safety of hepatic resection using the technique of stapler hepatectomy compared to the simple clamp-crushing technique. Methods/Design: The CRUNSH Trial is a prospective randomized controlled single-center trial with a two-group parallel design. Patients scheduled for elective hepatic resection without extrahepatic resection at the Department of General-, Visceral- and Transplantation Surgery, University of Heidelberg are enrolled into the trial and randomized intraoperatively to hepatic resection by the clamp-crushing technique and stapler hepatectomy, respectively. The primary endpoint is total intraoperative blood loss. A set of general and surgical variables are documented as secondary endpoints. Patients and outcome-assessors are blinded for the treatment intervention. Discussion: The CRUNSH Trial is the first randomized controlled trial to evaluate efficacy and safety of stapler hepatectomy compared to the clamp-crushing technique for parenchymal transection during elective hepatic resection. Trial Registration: ClinicalTrials.gov: NCT01049607